Factors associated with the anonymous reporting of lifetime domestic violence in a genitourinary medicine clinic: a patient self-reported questionnaire study. (May 2013) - Sanmani, L; Sheppard, Z A; Chapman, C
Summary: Domestic violence (DV) occurs frequently within the UK, with one in four women and one in six men experiencing DV during their life. DV is the leading cause of morbidity for women aged 19–44 years and is associated with sexual health problems. However, few data exist on the prevalence of DV in UK genitourinary (GU) medicine settings. An anonymous questionnaire was self-completed by patients (n = 476/500) attending Bournemouth GU medicine clinic during July 2009 to explore associations between lifetime DV and sociodemographic, sexual and behavioural factors. Overall, 21% (98/472) reported that they had ever been abused by a partner (12% [27/229] of men and 29% [71/243] of women). Logistic regression highlighted that being female, having children/dependants and use of illicit drugs were the most important factors associated with lifetime DV. Regular staff training on DV is recommended to increase awareness and signposting to relevant services.